PlexinA1 deficiency in BALB/cAJ mice leads to excessive self-grooming and reduced prepulse inhibition. (December 2020) - Jahan, Mst Sharifa; Ito, Takuji; Ichihashi, Sachika; Masuda, Takanobu; Bhuiyan, Md. Eliusur Rahman; Takahashi, Ikuko; Takamatsu, Hyota; Kumanogoh, Atsushi; Tsuzuki, Takamasa; Negishi, Takayuki; Yukawa, Kazunori
Abstract: PlexinA1 (PlxnA1) is a transmembrane receptor for semaphorins, a large family of proteins that act as axonal guidance cues during nervous system development. However, there are limited studies on PlxnA1 function in neurobehavior. The present study examined if PlxnA1 deficiency leads to behavioral abnormalities in BALB/cAJ mice. PlxnA1 knockout (KO) mice were generated by homologous recombination and compared to wild type (WT) littermates on a comprehensive battery of behavioral tests, including open field assessment of spontaneous ambulation, state anxiety, and grooming, home cage grooming, the wire hang test of muscle strength, motor coordination on the rotarod task, working memory on the Y maze alternation task, cued and contextual fear conditioning, anxiety on the elevated plus maze, sociability to intruders, and sensory processing as measured by prepulse inhibition (PPI). Measures of motor performance, working memory, fear memory, and sociability did not differ significantly between genotypes, while PlxnA1 KO mice displayed excessive self-grooming, impaired PPI, and slightly lower anxiety. These results suggest a crucial role for PlxnA1 in the development and function of brain regions controlling self-grooming and sensory gating. PlxnA1 KO mice may be a valuable model to investigate the repetitive behaviors and information processing deficits characteristic of many neurodevelopmental and psychiatric disorders.